Basic questions of genetics, stem cell research and cloning are these technologies okay to use? - Bevington, Linda K.; Bohlin, Ray G.; Centre for Bioethics and Human Dignity (Grand Rapids, MI Kregel, 2004)
Includes bibliographical references.
Keywords: Bioethics -- religious aspect -- Christianity